The world until yesterday : what can we learn from traditional societies? - Diamond, Jared M. (Viking, 2012)
Diamond reveals how tribal societies offer an extraordinary window into how our ancestors lived for millions of years -- until virtually yesterday, in evolutionary terms -- and provide unique, often overlooked insights into human nature.